Tipos de aleaciones metálicas utilizadas en la elaboración de prótesis parcial removible, revisión sistemática - Ruiz Sánchez, Edison Paul (2025)
Removable partial dentures (RPPs) are essential in oral rehabilitation, and the choice of suitable materials is crucial. Metal alloys have been widely used, but the search for more esthetic and biocompatible alternatives has driven research into new materials and fabrication techniques. We conducted a systematic review of studies published between 2018 and 2024, focusing on metallic alloys and alternative materials used in PPR fabrication, evaluating their mechanical properties, biocompatibility, durability, and corrosion resistance. The objective of this review was to provide a systematic review of the different metallic alloys used in the exposed studies. The results showed that the choice of alloy and fabrication technique significantly influence the performance of PPRs. Co-Cr, although widely used, can present challenges in terms of fit, while titanium and palladium-gold offer superior fit. Research in metal alloys for PPRs has advanced significantly, seeking solutions that optimize the precision, strength and durability of these prostheses. The choice of alloy and fabrication technique must consider several factors, including mechanical properties, biocompatibility, cost and esthetics.